CARRYING CAPACITY AND LAND SUITABILITY OF RICE FIELDS ON THE SPATIAL PLANNING OF PANGKAJENE URBAN AREA - Reza Asra; Andi Ayu Nurnawati; muhammad Faisal MF; Aksal Mursalat (Tunas Geografi, 2020)
The growth of an urban area will result in the conversion of agricultural land to non-agricultural land. In some cases, agricultural land that has the most opportunity to experience conversion is rice fields. The purpose of this study is to provide an overview of the condition of the rice fields related to the carrying capacity and its suitability to the urban spatial layout of Pangkajene. The method used in this research is a quantitative descriptive analysis of spatial data and secondary data. The area of rice fields in the urban area of Pangkajene in a vulnerable time of 7 years decreased by 149 ha. The results of the calculation of the carrying capacity of rice fields in the Pangkajene urban area in 2020 amounted to 0.27 which is included in class III or low criteria. While the optimal population is 11,102 people. The total of 15.23 ha of land was not suitable for the agricultural planning zone in regional spatial planning. There are still people who build buildings in the agricultural area of 2.99 ha or 0.71%. The open land also exists in the area designated for agricultural activities covering an area of 6.91 ha or 1.63%. The residents also expand their yards in an area devoted to agricultural activities by 5.33 ha or 1.26%.Keywords: Rice Fields, Carrying Capacity, Spatial Planning, Geographic information system